The polarized “naturalizations” of the 2022 Freedom Convoy - Mélissa Roy; Ari Gandsman; Nathalie Plante (Discover Global Society, 2024)
Abstract During the month-long “Freedom Convoy” protest in Ottawa (Canada), protesters were ascribed many attributes (violent, extremist, hateful, disinformed) which they refuted. Protest organizers insisted the Freedom Convoy was peaceful, loving, and included “average Canadian citizens fighting for freedom”. This research is interested in the construction of this representational divide and its consequences. It analyzes the polarized social representations of the COVID-19 Freedom Convoy by using social representation theory, and more specifically, Negura and Plante’s model of “naturalization”. News articles (n = 516) from Canadian media and Freedom Convoy organizers’ Facebook posts (n = 611) were submitted to a rhetorical frame analysis. Results show how communications from organizers and the media both contributed to the naturalization of conflicting representations by (1) associating the movement with a desirable/undesirable identity, (2) neglecting nuanced perspectives, (3) instrumentalizing their representation to justify the legitimacy/illegitimacy of the protest, and (4) validating the representation by focusing on incidents that ratified the Freedom Convoy’s “goodness” or “badness”. We argue that this single protest became two opposed and morally charged “objects” impossible to reconcile, which prevented dialogue. Social implications of polarized naturalizations during epidemics are discussed.